Comparing the Utility of Capture–Mark–Recapture, Telemetry, and Genetic Data in Assessing Population-Level Dispersal - Shashwat Sirsi; Brian J. Halstead; Michael L. Morrison; M. Clay Green; David Rodriguez; Michael R. J. Forstner (Diversity)
Gaps in dispersal data limit habitat protection efforts. We sought to characterize such gaps and compare the utility of dispersal data from demographic and genetic methods in making habitat protection decisions. Here, we used a search string to retrieve dispersal studies for amphibians, reptiles, birds, and mammals. We included studies based on a set of selection criteria. We used this sample of selected studies to assess for persistence of taxonomic and geographic biases. We extracted non-effective (i.e., demographic) and effective (i.e., genetic) dispersal rates. We weighted these dispersal rates by associated sample size and standard deviation to indicate the ability to capture population-level dispersal. We then tested for variation in weighted dispersal by study type using Bayesian mixed-effects models. Amphibians were the most under-represented taxonomic group in our sample. Dispersal studies were mostly retrieved from developed nations indicating the distribution of dispersal research reflected GDP rather than the number of threatened species. The magnitude of dispersal from genetic methods exceeded demographic methods in all vertebrate groups considered in our study. Further, genetic studies consistently sampled a larger number of individuals. Thus, genetic methods may be better suited to characterize population-level dispersal. However, demographic and genetic approaches enable examination of the dispersal process at varying spatial and temporal scales and a combination of these approaches can be used to address persistent gaps in dispersal and enable land-management decisions.